Mengembangkan Kewirausahaan Berbasis Pastoral Dengan Menggunakan 7 Langkah Pekerjaan Pastoral - Kristeno, Marianus Rago; Tarihoran, Emmeria (SAPA - Jurnal Kateketik dan Pastoral, 2025)
Pastoral entrepreneurship is an innovative approach that integrates spiritual values ​​with efforts to empower the people's economy. The Catholic Church uses this concept to help people become financially independent, strengthen community solidarity, and increase prosperity based on Gospel values. This research explores the application of the 7 Steps of Pastoral Work, from introduction to evaluation, which enable the Church to plan and manage entrepreneurship programs systematically. By using the library study method, researchers try to collect literary sources such as Church documents, scientific articles, and books that are relevant to the research, then integrate certain themes to draw conclusions. The results show that pastoral entrepreneurship contributes significantly to increasing people's income, creating jobs, and strengthening spiritual values. However, its implementation faces challenges, such as limited resources, lack of entrepreneurial skills, and people's resistance to change. To overcome these obstacles, a strategic approach, ongoing training and cooperation between parties is needed. By integrating economic and spiritual aspects, pastoral entrepreneurship has the potential to be an effective means for the Church to empower people as a whole and create sustainable prosperity in the community.